Learning media development physical education sport and health that number athletic material based on Android application - Syukron Zuhdi; Yustinus Sukarmin (Nicolaus Copernicus University in Toruń, 2021)
This study aims to (1) produce development products for physical education sport and health learning media based on android applications on the athletic material of throwing numbers for high school students, (2) to find out the feasibility of developing learning media products for physical education sport and health learning media based on android applications on throwing number athletic materials for high school students and (3) determine the level of effectiveness of the development of learning media products for physical education sport and health based on android applications on athletics throwing numbers for high school students. This research and development are carried out in ten stages which refer to the steps developed by Borg & Gall, which include: (1) Research and information gathering, (2) Planning, (3) Initial product development, (4) Improvement of the initial design, (5) Formation of trial products, (6) Small group trials, (7) Revision of small group trial products, (8) Field trials, (9) Revision of field trial products, (10) Dissemination or dissemination. The subjects of the small group trial were 21 students of class XI SMA N 5 Yogyakarta, the subjects of the field trials were 112 students of class XI SMA N 8 Yogyakarta, the product trials included material expert trials, media experts, and small group trials and field trials. by students. Data obtained through observation, questionnaires, interviews, and learning outcomes tests. Data analysis used a t-test with a significance level of 0.05. Based on the results of the pretest and posttest that have been obtained, then the effectiveness test was carried out using the paired sample t-test using the SPSS program. 16 For Windows. The results of the research of the pretest and posttest data on the field test showed that the learning media had a significant effect on improving student or respondent achievement. The effectiveness of learning media can be seen in the descriptions of the results of the pretest and posttest on respondents or students of SMA N 8 Yogyakarta as follows. At the pretest the lowest score got a score of 33.00, then the highest score got a score of 100.00. The average number of values on the pretest reached 79.91, and if all the respondents' scores on the pretest were added up to reach a value of 8951.00. After being treated with the application of learning media, the lowest score in the posttest increased to 37.00 and the highest score reached a maximum score of 100.00. The average overall score on the posttest increased to 86.62, and the total score at the posttest reached a score of 9702.00. Thus, it can be concluded that the instructional media products of physical education sport and health, athletic number throwing materials based on android applications can be used by students and teachers as a medium in the teaching and learning process. Keywords: learning media, athletics throwing numbers, android applications